Pengaruh Implementasi Akuntansi Berbasis Akural dan Sistem Pengendalian Internal Terhadap Akuntabilitas Kinerja Instansi Pemerintahan pada Lembaga Manajemen Aset Negara - Aprilia, Gladys Dwika; Ramadhan , Puja Rizky; Hanafi, Hanafi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The study aims to determine the effect of the implementation of accrual-based accounting and internal control systems on the accountability of performance in government institutions at the State Asset Management Agency. The type of research used is associative research method with the help of SPSS version 19. This study employs multiple linear regression analysis. The sample in this study consists of 92 respondents. Primary data collection was conducted using a questionnaire. The research results indicate that accounting standards have a positive and significant partial effect on the accountability of government performance in the State Asset Management Agency. The test results show a t-count value of 4.554 > t-table value of 1.98 with a significance value of 0.000 < 0.05, therefore, hypothesis H2 is accepted and H0 is rejected, meaning that the internal control system has a positive and significant partial effect on the accountability of government performance in the State Asset Management Agency. The research results show that accrual-based accounting and internal control systems have a positive and significant effect on performance accountability with an F-count value of 16.521, which is greater than 3.10, and a significance value of 0.000 which is less than 0.05.